To transform the function \( f(x) = 3x \) to \( -f(3x-2) + 1 \), we follow these steps using proper order of operations (often remembered as PEMDAS: Parentheses, Exponents, Multiplication and Division (from left to right), Addition and Subtraction (from left to right)).
- Start with the original function:
\( f(x) = 3x \)
Now we will apply the transformations step-by-step to show how to get to \( -f(3x - 2) + 1 \).
Table Steps
| Step # | Expression | Operation | |---------|--------------------------------|--------------------------------| | 1 | \( 3x \) | Original function \( f(x) \) | | 2 | \( 3(3x - 2) \) | Substitute \( 3x-2 \) into \( f(x) \) | | 3 | \( 9x - 6 \) | Multiply \( 3 \times (3x - 2) \) | | 4 | \( -(9x - 6) + 1 \) | Apply the negative sign and add 1 | | 5 | \( -9x + 6 + 1 \) | Simplify to \( -9x + 7 \) |
Evaluating the Expressions
Now let's evaluate the expressions based on input \( x \):
Assume we are evaluating this transformation at \( x = 1 \).
-
Original: \[ 3(1) = 3 \]
-
Step 2: \[ 3(3(1) - 2) = 3(3 - 2) = 3(1) = 3 \]
-
Step 3: \[ 9(1) - 6 = 9 - 6 = 3 \]
-
Step 4: \[ -(9(1) - 6) + 1 = -(3) + 1 = -3 + 1 = -2 \]
-
Step 5: \[ -9(1) + 6 + 1 = -9 + 6 + 1 = -3 + 1 = -2 \]
Summary
The final evaluation would thus transform \( f(1) = 3 \) into \( -f(3(1)-2) + 1 = -2 \).
Please note, if you need to replace \( x \) with other values, you'll repeat similar computations for each value. If you indicate specific values for \( x \) for this table, I can help calculate those as well!